Pengembangan Model Prediksi Aktivitas Fisik Berdasar Prediktor Sosial Kognitif pada Pelajar: Model Prediksi Aktivitas Fisik - Mz, Afrizul; Arovah, Novita Intan (Faculty of Sport and Health Sciences, 2023)
Physical inactivity is a significant public health concern among adolescents. Social cognitive factors are suggested to influence physical activity including in students, However, it is unclear how these factors influence physical activity levels among students in the Education and Training Center in Riau. This study aimed to develop a prediction model of physical activity levels based on social cognitive predictors in this population. The study was a cross-sectional study of 107 students from the Education and Training Center in Riau who completed online questionnaires on physical activity and social-cognitive correlates. Physical activity levels were measured using the Physical Activity Vital Sign, while the social cognitive correlates included self-efficacy, outcome expectations, stress levels, and motivation, which were measured using validated scales. Simple and multiple linear regression analyses were conducted to analyze the data. The results indicated that self-efficacy, outcome expectations, stress levels, and motivation significantly predicted physical activity levels among students. The results of the multiple linear regression indicated regression coefficients were 0.26, 0.31,-0.33 and 0.27 for self-efficacy, outcome expectation, stress level and motivation practice, respectively. The multiple linear regression model, which included all variables, predicted 32.9% of the variance in physical activity levels. The findings suggest that physical activity promotion programs for students should focus on improving self-efficacy, outcome expectations, stress management, and motivation. Future research can focus on developing and evaluating the efficacy of physical activity promotion interventions that target social cognitive predictors among students.